Hair cortisol and self-reported stress in healthy, working adults. (January 2016) - Gidlow, Christopher J.; Randall, Jason; Gillman, Jamie; Silk, Steven; Jones, Marc V.
Highlights: Hair cortisol concentrations (HCC) were compared with a range of self-reported stress measures. HCC was not associated with stress from ecological momentary assessment, recall or effort-reward. A modest HCC-stress appraisal association may implicate cognitive processes in chronic stress. Efforts should focus on HCC as a biomarker of disease risk, regardless of self-reported stress. Abstract: Chronic stress can be important in the pathology of chronic disease. Hair cortisol concentrations (HCC) are proposed to reflect long term cortisol secretion from exposure to stress. To date, inconsistencies in the relationship between HCC and self-reported stress have been attributed to variation and limitations of perceived stress measurement. We report data from employees of two large public sector worksites ( n  = 132). Socio-demographic, health, lifestyle, perceived stress scale (PSS), and work-related effort reward imbalance (ERI) were collected at baseline. Participants were asked to respond to mobile text messages every two days, asking them to report current stress levels (Ecological momentary assessment, EMA), and mean stress was determined overall, during work hours, and out of work hours. At 12 weeks, the appraisal of stressful life events scale (ALES) was completed and 3 cm scalp hair samples were taken, from which HCC was determined (to reflect cortisol secretion over the past 12 weeks). Mean response rate to EMA was 81.9 ± 14.9%. Associations between HCC and the various self-reported stress measures (adjusted for use of hair dye) were weak (all < .3). We observed significant associations with HCC for EMA measured stress responses received out of work hours ( ρ  = .196, p  = .013) and ALES Loss subscale ( ρ  = .241, p  = .003), and two individual items from ERI (relating to future work situation). In regression analysis adjusting for other possible confounders, only the HCC-ALES Loss association remained significant ( p  = .011). Overall, our study confirms that EMA provides a useful measurement tool that can gather perceived stress measures in real-time. But, there was no relationship between self-reported stress collected in this way, and HCC. The modest association between HCC and stress appraisal does however, provide some evidence for the role of cognitive processes in chronic stress.